2012
DOI: 10.1007/s12011-012-9490-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Occupational Lead Exposure on Blood Levels of Zinc, Iron, Copper, Selenium and Related Proteins

Abstract: The study objective was to evaluate the effect of occupational lead exposure on blood concentrations of zinc, iron, copper, selenium and proteins related to them, such as transferrin, caeruloplasmin and haptoglobin. The examined group consisted of 192 healthy male employees of zinc–lead works. By the degree of lead exposure, the exposed group was subdivided into three subgroups. The control group was composed of 73 healthy male administrative workers. The markers of lead exposure (blood levels of lead and zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 47 publications
5
39
0
1
Order By: Relevance
“…In this study serum lead (Pb) level was higher in the traffic policemen than the control. Evidence from previous studies also supports this observation [13][14][15] . But some studies do not support this 16 .The correlation analysis in this study between FEV 1 , FVC, FEV1/FVC ratio and serum lead level in TP showed negative relationship though statistically was not significant.…”
Section: Discussionsupporting
confidence: 82%
“…In this study serum lead (Pb) level was higher in the traffic policemen than the control. Evidence from previous studies also supports this observation [13][14][15] . But some studies do not support this 16 .The correlation analysis in this study between FEV 1 , FVC, FEV1/FVC ratio and serum lead level in TP showed negative relationship though statistically was not significant.…”
Section: Discussionsupporting
confidence: 82%
“…Lead can not only generate reactive oxygen species (ROS), but also be able to deplete antioxidant reserves (6). Furthermore, elevated levels of ALA, characteristic of plumbism, generate hydrogen peroxide and superoxide radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Altered RBC counts and eryptosis are common in occupationally Pb-exposed workers [33][34][35]. Intriguingly, due to its adverse effects on RBCs, Pb exposure has recently been considered a pathogenetic factor for chronic cardiovascular and renal diseases [36,37].…”
mentioning
confidence: 99%